Identification and classification of the implementation of knowledge management factors in Malaysian construction consulting companies : an exploratory study - Rasli, Amran; Ade Asmi, Ade Asmi; Abd. Majid, M. Z. (Universiti Utara Malaysia, 2006)
Ever since knowledge has become an important corporate asset, Knowledge Management (KM) has become a critical concern for construction consulting companies to create and sustain their competitive advantage. Therefore, an exploratory research was conducted to identify and classify the methods of implementing key KM faktors in Malaysian construction consulting companies using a three-round Delphi technique study to identify and rank critical components of Knowledge Management (KM) principles for construction consulting companies. Subsequently, faktor analysis was used to generate variables for the KM faktors and the results are compared with the original groupings identified from the first level of the research. Finally, the classification of the implementation of KM faktors are analysed and further grouped into two categories i.e., exploitive and explorative. A one sample ttest was conducted to confirm the difference between the two types of KM and the overall the KM program.